The effects of goal priming on cortisol responses in an ego-involving climate. (September 2017) - Breske, Michael P.; Fry, Mary D.; Fry, Andrew C.; Hogue, Candace M.
Abstract: Objectives: This study examined the potential for a motivational priming session to buffer the psychophysiological stress response to an ego-involving climate in a physical activity setting. Research in Achievement Goal Perspective Theory (AGPT) suggests that creating a caring/task-involving climate can have beneficial effects on participants in physical activity settings, even buffering the physiological response to stress. However, less is known about how individuals might buffer that response when an ego-involving climate is occurring beyond their control. Design: Male college students (N = 38) between the ages of 18 and 30 years ( M age = 20.68, S D = 2.66 ) were randomly assigned to either a control group with no exposure to AGPT or an experimental (i.e., AGPT motivational priming) group, and took part in an ego-involving juggling session. Psychophysiological stress responses (e.g., cortisol) were assessed. Method: Prior to juggling, the experimental group received a motivational priming session that briefly reviewed the body of AGPT literature, while the control group received information on the history of Sport Psychology as a professional field. Cortisol was measured at five time points throughout the study via saliva samples. Participants also completed pre- and post-measures of self-reported anxiety and self-confidence (CSAI-2). Results: Results showed a marked increase in cortisol (as measured by percent change from baseline) in the control group, but not the experimental group. Psychological responses were stable across groups. Conclusion: Providing athletes and exercisers with nothing more than basic information on AGPT can reduce their physiological markers of psychosocial stress in ego-involving climates. Such education may be a beneficial practice for coaches, physical educators, and trainers. Highlights: Many individuals experience ego-involving climates in sport contexts. Learning a new skill in an ego-involving climate can elicit a cortisol response. Providing a motivational priming session can help buffer this cortisol response.